The Law of Adoption of Children Out of Wedlock in the Perspective of Islamic and Indonesian Law - Amar Yusuf Abdurrohman; Misbahuzzulam; Muhammad Husni Abdulah Pakarti; Imran Ahmad Sajid; Fateema Muslihatun Najihah (Yayasan Cendekia Gagayunan Indonesia, 2025)
The adoption of children from extramarital relationships is a complex legal issue because it involves legal, social, and religious dimensions at the same time. This study aims to analyze the comparison of the regulation of adoption of children out of wedlock in Islamic law and positive law in Indonesia, especially related to the legal status of children, civil relations, and the implications of their rights. This research uses a normative-juridical approach with a comparative legal method, through an examination of laws and regulations, court decisions, fatwas, as well as relevant Islamic law and national law literature. The results of the study show that in Indonesia's positive law, children out of wedlock can obtain a civil relationship with their biological father as long as it is scientifically proven and determined through legal mechanisms, but does not automatically obtain inheritance rights from adoptive parents except through grants or mandatory wills. Meanwhile, Islamic law views the adoption of children in the form of kafālah, which emphasizes the parenting aspect without changing the child's nasab, inheritance rights, and marital status. The difference in principle between the two legal systems poses normative challenges in the practice of child protection, so an integrative approach is needed that is able to ensure the best interests of children without ignoring Islamic sharia values. This research contributes by offering a conceptual framework for harmonization between Islamic law and national law in the regulation of out-of-wedlock child adoption based on the protection of children's rights.